Effects of SARS Cov-2 epidemic on the obstetrical and gynecological emergency service accesses. What happened and what shall we expect now?. (November 2020) - Dell'Utri, Chiara; Manzoni, Elisabetta; Cipriani, Sonia; Spizzico, Claudio; Dell'Acqua, Andrea; Barbara, Giussy; Parazzini, Fabio; Kustermann, Alessandra
Abstract: Objective: During the lockdown period, the fear about the risk of infection in hospital has reduced the admission to Emergency Services (ES) with possible negative health effects. We have investigated the changes in the emergency flow occurred during SARS-CoV-2 pandemic in an obstetrics and gynecological ES and the short-term adverse outcomes on women's and reproductive health. Study design: The study was conducted in the OBGYN ES of the Clinica Mangiagalli, the largest maternity clinic of Milan, Lombardy, Northern Italy. We analyzed retrospectively the records of all women consecutively admitted at the ES from February 23rd to June 24th 2019, and compared them with the admissions during the lockdown executive order from February 23rd to June 23rd, 2020. Patients were assessed in terms of demographic features, presentation times, triage classification (urgent/not urgent), reason for admission and outcome of the visit (discharge/admission to the ward). A total of 9291 data were retrieved from ES files and automation system, 5644 from 2019 and 3647 from 2020. Categorical variables were compared by the chi-square test calculating the p value and computed were percentage changes (with 95 % Confidence interval, CI). Results: During the period February 24 th - May 31 th 2020 the admissions at the ES decreased by 35.4 % (95 % CI—34.1–36.6) compared with the corresponding period in 2019. The reduction was more marked for gynecological complaints (-63.5 %, 95 %CI -60.5 to -66.5): in particular we observed a reduction of admissions for genital infection/cystitis of 75.7 % (95 %CI -71.4 to -80.1). The admission for complaints associated with pregnancy decreased by 28.5 % (95 %CI -27.2 to-29.9). In the index period, five fetal deaths were diagnosed compared with one observed in the reference period in 2019 (chi square computed using as denominator all observed pregnancies = 4.29, p = 0.04). The frequency of admission for elective caesarean section/labor induction increased from 47.5 % in 2019 to 53.6 % in 2020: this difference was statistically significant. Conclusion: The lockdown negatively influenced ES admissions and consequently the women's/reproductive health. As possible short-term consequences, we observed an increase of intrauterine deaths and a decrease of natural births.